Gastrointestinal sarcoidosis presenting with malabsorption at an early age - (:unkn) unknown (My University, 2020)
Sarcoidosis is a chronic multisystemic granulomatous disease that predominantly involves the thoracic lymph nodes and lungs and primarily occurs in young adults. Isolated extrapulmonary localization is uncommon in adults, and exceptionally rare in the pediatric age group. A 4-year-old male patient with chronic diarrhea and abdominal distention for the last 8 months is presented. Endoscopic biopsies, obtained during gastroscopy and colonoscopy, revealed noncaseating granulomas in all segments of the gastrointestinal tract. A noncaseating granuloma was also demonstrated in the liver biopsy. Granulomatous inflammation of both the gastrointestinal system and liver along with elevated serum angiotensin-converting enzyme were consistent with sarcoidosis. The peculiarity of our pediatric sarcoidosis was the involvement of whole gastrointestinal system, which is exceptionally rare in all age groups. Furthermore, this is the youngest case in the literature with gastrointestinal and hepatic sarcoidosis in the absence of pulmonary involvement at onset.

Sarkoidoz, ağırlıklı olarak torasik lenf nodları ve akciğerleri tutan bir kronik multisistemik granülomatöz hastalıktır ve çoğunlukla genç eriş?kinlerde görülür. İzole ekstrapulmoner tutulum erişkinlerde sık görül?memekle birlikte çocukluk yaş grubunda çok daha nadirdir. Son 8 aydır kronik ishal ve abdominal distansiyonu olan 4 yaşında bir erkek hasta su?nuldu. Gastroskopi ve kolonoskopide alınan biyopsilerde, gastrointesti?nal sistemin tüm segmentlerinde nonkazeifiye granülomlar tespit edildi. Ayrıca, karaciğer biyopsisinde de nonkazeifiye granülom saptandı. Hem gastrointestinal sistemin hem de karaciğerin granülomatöz inflamasyo?nu, anjiotensin-dönüştürücü enzim yüksekliği ile birlikte değerlendiril?diğinde sarkoidoz ile uyumlu görüldü. Pediatrik sarkoidoz olgumuzun en önemli özelliği, tüm yaş gruplarında son derece nadir görülen gastro?intestinal sistem tutulumunun vakamızda yaygın olarak saptanmasıydı. Ayrıca bu olgu başlangıçta akciğer tutulumu olmadan, gastrointestinal ve hepatik tutulumun birlikte görüldüğü dizindeki en genç olgudur.
Erken yaşta malabsorbsiyon ile ortaya çıkan gastrointestinal sarkoidoz olgusu